OLED display fundamentals and applications - Tsujimura, Takatoshi (John Wiley & Sons Inc., 2017)
"This book covers the aspects necessary to the design and manufacturing of OLED displays. Topics include emission mechanism, material selection, device processing, manufacturing issues and countermeasures and display design basics. In addition, the book defines elements of OLED such as Thin Film Transistor (TFT) backplane design and processing details, including Low Temperature Poly Silicon (LTPS) process and circuit integration, and high yield method to manufacturer. Researchers and developers are aiming at making large OLED televisions and companies such as Samsung and Apple are rumored to be using OLED display for new screens. In addition to discussing the current composition of OLED, the book also discusses the future for OLED technologies and displays. The new edition examines the most recent information available and also reinforces the content of the previous edition"--